(untitled) (Journal of Parents and Teachers, 2014)
Different methods try to reach the same end, teaching and educating, not all are equally effective but some, such as environmental education, facilitate the understanding of its content through the use of everyday elements. Although this variant is fashionable, it is not something new, but since the 1950s Freman Tilden has been providing information in his articles through elements that are easy to understand. In order to be a successful and optimum tool for the development of students, environmental education must be based on a pleasant, relevant, organised and focused interpretation of a specific topic.